Modelo de previsão e controle da podridão floral dos citrus causada por Colletotrichum acutatum - Peres, Natália Aparecida Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2002)
A podridão floral, causada por Colletotrichum acutatum, afeta flores de citros e induz à abscisão de frutos jovens, sendo considerada um sério problema na maioria das áreas úmidas onde se produz citros nas Américas. O controle da doença é feito pela pulverização de fungicidas durante a florada porém, uma das dificuldades é determinar o momento ideal para o controle. Um modelo de previsão foi desenvolvido na Flórida para indicar a necessidade de pulverização, considerando a quantidade de inóculo, chuvas e molhamento foliar. Este modelo foi avaliado durante três anos consecutivos na região de Itapetininga-SP. Verificou-se que mediante a aplicação do modelo obteve-se um bom controle da doença, tendo-se evitado duas pulverizações desnecessárias em comparação com o calendário, em 1999, e uma pulverização, comparado ao esquema do produtor, em 2000 e 2001. Um novo sistema de previsão para controle da podridão floral (PFD-FAD) foi desenvolvido incorporando outros fatores que também influenciam a ocorrência da doença, como o histórico do pomar, a suscetibilidade da variedade, o estágio de desenvolvimento da florada, assim como chuva, molhamento foliar e nível de inóculo, além da data da última... .

Postbloom fruit drop (PFD), caused by Colletotrichum acutatum Simmonds, infects petals of citrus flowers and induces the abscission of fruitlets. The disease can cause serious losses in most humid areas where citrus is produced in the Americas. The disease is controlled by fungicide applications during the bloom but it is difficult to properly time applications. A model was developed in Florida to schedule fungicide applications based on the amount of inoculum and the amount of rainfall and leaf wetness for the last 5 days. This model was evaluated during three consecutive years in Itapetininga-SP, Brazil. Results showed that applications following the model provided good control of the disease and saved two sprays compared to the calendar program in 1999, and one spray compared to the grower’s choice in 2000 and 2001. A new advisory system (PFD-FAD) was developed to be more widely applicable by incorporating risk factors that are inherent in any planting which affected by PFD incidence. The history of the disease in the grove, the varietal susceptibility, the stage of the bloom, as well as the rain, leaf wetness, the amount of inoculum and the last spray date were considered. Field tests in 2001 showed that the system provided good control of the disease with only one fungicide application. Benomyl is considered one of the most effective products for PFD control but despite that C. acutatum is not highly sensitive to benomyl in culture. The mycelial growth and conidial germination is inhibited by 80% at concentration of 1.0 μg/mL, but higher concentrations do not completely inhibit the growth of the fungus. Colletotrichum gloeosporioides, a common saprophyte and causal agent of anthracnose of fruits postharvest, is completely inhibit by 1.0 μg/mL... (Complete abstract, click electronic address below).
Keywords: Fitopatologia; Cítricos; Colletotrichum acutatum